THE IMPACT OF COMPUTER ANXIETY, PERSONAL INNOVATIVENESS IN INFORMATION TECHNOLOGY, AND COMPUTER EXPERIENCE ON COMPUTER SELF-EFFICACY - Suwardi, Bentarani; Baridwan, Zaki (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aims  to  analyze the relationship between  computer  anxiety, personal  innovativeness  in information technology,  and  computer experience on computer self-efficacy as well as the relation between personal  innovativeness  in information technology and computer experience with computer anxiety, and  the level of computer anxiety based on gender for accounting students. The research is  in the domain  of  information  technology  and  humanistic  viewpoint  on personality traits based on social cognitive theory.It is  quantitative  research  using  primary data  from  116 respondents  of accounting students with 71% female. The survey questionnaires are distributed to 302 students of accounting directly at the end of the class, which are collected for one month.The results of the research data and hypothesis testing using  Structural Equation Modeling  (SEM) based on  Partial  Least  Squares (PLS) and  Social Science Statistical Package (SPSS) shows that computer anxiety (ANX) has direct negative effect  to computer self-efficacy (CSE),  personal innovativeness  in information technology  (PIT) has direct positive effect  to computer self-efficacy (CSE), and personal innovativeness in  information technology  (PIT)  and computer experience  (CEX)  has  direct  negative  effect  to  computer anxiety (ANX), and computer anxiety (ANX) average  level of female  is higher  than  that of male.